Mối quan hệ thể chế và khả năng tiếp cận thị trường vốn của doanh nghiệp - Vu Viet, Quang; Le Thi Phuong , Vy (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2016)
As suggested by earlier studies, with political connections some firms receive more preference than others (Fisman, 2001; Johnson & Mitton, 2003; Faccio, 2006). Using a dataset of listed joint-stock companies on HNX and HOSE between 2009 and 2013 besides adopting the panel regression technique, we find empirical evidence of political connections with their role in improving firms’ access to finance, especially from state commercial banks. This result also underpins the assumption that political connections do give firms certain preference, help remove legal constraints and/or barriers as well as the problem of information asymmetry, thereby enhancing their ability to have access to the capital market.
Keywords: Political connections; debt ratio; access to finance